How to Choose the Appropriate Posterior Slope Angle Can Lead to Good Knee Joint Function Recovery in Total Knee Arthroplasty? - Pan XQ; Liu JH; Zhang JL; Chai A; Li F; Shu L; Zhao W (Therapeutics and Clinical Risk Management, 2023)
Xi-Qing Pan, Jin-Hui Liu, Jiang-Li Zhang, An Chai, Feng Li, Lei Shu, Wei Zhao Department of Joint Surgery, Third Hospital of Shijiazhuang, Shijiazhuang, Hebei, People’s Republic of ChinaCorrespondence: Jin-Hui Liu, Department of Joint Surgery, Third Hospital of Shijiazhuang, No. 15 Tiyu South Street, Shijiazhuang, Hebei, 050011, People’s Republic of China, Tel +86 13191872146, Fax +86 31185990628, Email jinhuiauliu6@126.comObjective: In this study, we aim to examine the effects of osteotomy under varying posterior slope angles on knee joint function recovery following knee arthroplasty.Methods: We conducted a retrospective analysis from September 2015 to September 2018 on 240 patients who underwent knee arthroplasty three years previously. The study participants were categorized based on changes in the angle of the posterior slope before and after surgery: Group 1, > 5°; Group 2, 3°– 5°; Group 3, 0°– 3°; Group 4, − 3°– 0°; Group 5, < − 3°. All participants were affected with knee osteoarthritis. The Knee Society Clinical Rating System (KSS) knee function score, Western Ontario and McMaster Universities Arthritis Index (WOMAC) knee function score, Visual Analogue Scale (VAS) pain score, and postoperative complications were measured 3 years after surgery.Results: The level of pain experienced by the patients decreased significantly than before, with pain scores ranging from 1.0– 3.0, and there was a statistical difference between groups (H = 93.400, P